La autoría femenina y la construcción de la identidad en Crónica del Desamor de Rosa Montero - Montero Rodríguez, Shirley (2007)
The reflection of this work establishes the possibility of discovering a place for literature written by women, explicitly when it is constructed by means of elements proper of the feminine space, with its specific world perspective and from its own circumstances in life. First, it will present the preliminary aspects that will locate this work in the most important historical, cultural and social context. This may allow to handle a global panorama of feminine literature production in Spain, during the last quarter of the XXth Century. Furthermore, the theoretical perspective will be joined in this section, as a frame for general reflections. In the second section, it is intended to formulate an analysis, so to establish the discursive configuration of the voice of feminine authorship.